Anticancer Activity of Novel Thiophenes Containing a Biological Active Diphenylsulfone, Diazepin, Piperidine, Oxazepine, Acryladehyde and Sulfonamide Moieties - AlSaid, M. S.; El-Gazzar, M. G.; Ghorab, M. M. (Drug Research, 2013)
A variety of thiophene derivatives bearing diphenylsulfone 3,4, diazepines 5b, 6b, phenylamino 7, piperidine 8, benzylpiperidine 9, oxazepines 10b, 11b, acrylaldehydes 12–14 and benzeonesulfanamide 15 were synthesized. some newly synthesized compounds were evaluated for their in vitro cytotoxic activity against human tumor breast cancer cell lines. The tested compounds showed moderate to good cytotoxic activity and indeed, some of them were more potent than doxorubicin as a reference drug.
Keywords: thiophenes; sulfone; diazepine; piperidine; oxazepine; acryladehyde; sulfonamide; cytotoxic activity